Inner and Outer Horizons of Time Experience - Wackermann, Jirí (The Spanish Journal of Psychology, 2007)
Human experience of temporal durations exhibits a multi-regional structure, with more or less distinct boundaries, or horizons, on the scale of physical duration. The inner horizons are imposed by perceptual thresholds for simultaneity (≈3 ms) and temporal order (≈30 ms), and are determined by the dynamical properties of the neural substrate integrating sensory information. Related to the inner horizon of experienced time are perceptual or cognitive “moments.” Comparative data on autokinetic times suggest that these moments may be relatively invariant (≈102 ms) across a wide range of species. Extension of the “sensible present” (≈3 s) defines an intermediate horizon, beyond which the generic experience of duration develops. The domain of immediate duration experience is delimited by the ultimate outer horizon at about ≈102 s, as evidenced by analysis of duration reproduction experiments (reproducibility horizon), probably determined by relaxation times of “neural accumulators.” Beyond these phenomenal horizons, time is merely cognitively (re)constructed, not actually experienced or “perceived,” a fact that is frequently ignored by contemporary time perception research. The nyocentric organization of time experience shows an interesting analogy with the egocentric organization of space, suggesting that structures of subjective space and time are derived from active motion as a common experiential basis.
Keywords: Autokinetic tim; Dual klepsydra mode; Duration reproduction; Phenomenal horizon; Psychophysics; Subjective time; Temporal experience